TiB2-reinforced composite coating by gas tungsten arc welding - Yilmaz, S. O.; Ozenbas, M. (Springer, 2009)
In situ synthesized TiB2-reinforced Fe-based coating was fabricated by gas tungsten arc welding (GTAW) on AISI-4340 steel substrate using cheaper Fe-Ti, Fe-Cr, Fe-W, Fe-B alloys and B2O3 powders. The effects of processing parameters on the coating were investigated experimentally. Primary dendrites of ferrite (alpha) phase and complex TiB2, Fe2B borides were detected at the coated surface. The experimental results show that either coated surface or interface microstructures were formed by the distribution of particularly boron and titanium concentration. The difference in hardness of the microstructures is specifically attributed to the type of borides. The type, dimension, and the volume concentration changes of borides were correlated with the parameters as the concentration of additives and the dilution from the base material. The surfaces were subsequently characterized by scanning electron microscopy (SEM), the energy dispersive X-ray spectrometry (EDS), X-ray diffraction (XRD), and differential thermal analysis (DTA).
Keywords: Wear Behavior; Mechanical-Properties; Matrix Composites; Tic Composites; Abrasive Wear; Carbon-Steel; Laser; Fe; Microstructure; Tib2